2016
DOI: 10.5202/rei.v7i2.222
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Natural Disasters: A Regression Meta-Analysis

Abstract: With a meta-regression analysis of the existing literature on the impacts of disasters on households, we observe several general patterns. Incomes are clearly impacted adversely, with the impact observed specifically in per-capita measures. Consumption is also reduced, but to a lesser extent than incomes. Poor households appear to smooth their food consumption by reducing the consumption of non-food items; in particular health and education, and this suggests potentially long-term adverse consequences. Given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…They cannot cut back on luxury consumption or delay consumption the way wealthier households can. In many countries they are close to the subsistence level, which means that reducing consumption can have immediate negative impacts on health (if food intake is reduced or medical care becomes unaffordable), education (if children are taken out of school), or economic prospects (if essential assets have to be sold) (Karim and Noy 2016). These consumption cuts have a large impact on immediate well-being, but can also affect human capital through health or education, creating long-term consequences on income and prospects (see below).…”
Section: Consumption Patterns and Food Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…They cannot cut back on luxury consumption or delay consumption the way wealthier households can. In many countries they are close to the subsistence level, which means that reducing consumption can have immediate negative impacts on health (if food intake is reduced or medical care becomes unaffordable), education (if children are taken out of school), or economic prospects (if essential assets have to be sold) (Karim and Noy 2016). These consumption cuts have a large impact on immediate well-being, but can also affect human capital through health or education, creating long-term consequences on income and prospects (see below).…”
Section: Consumption Patterns and Food Securitymentioning
confidence: 99%
“…Many studies have demonstrated that after a disaster (floods, hurricane, and storm), poverty tend to increase (Karim and Noy 2016). For instance, in Bolivia, the incidence of poverty climbed by 12% in Trinidad City after the 2006 floods, a fivefold increase compared with the national average (Perez-De-Rada and Paz 2008).…”
Section: Vicious Circles: Why Do Natural Disasters Keep People In Povmentioning
confidence: 99%
“…The natural disaster literature already includes several regression meta-analyses; e.g. [ 17 18 ]. Still, the literature on the long-term impact of economic shocks is relatively sparse, but the weight of the evidence suggests no lasting impact of even catastrophic shocks at the national level [ 19 ] but significant impacts at more local/regional levels in terms of even very long-term recovery–[ 20 ] analyses the impact of an event 50 years after the fact.…”
Section: Research On the 1995 Kobe Earthquakementioning
confidence: 99%
“…Given that poor people have consumption closer to subsistence, a substantial loss from floods in the absence of support can have high non-monetary costs in the form of irreversible impacts on children and distress sales of assets (de Janvry et al 2006;World Bank and Australian AID 2014). In summary, livelihood shocks triggered by floods could keep people from escaping poverty and even push them into deeper poverty (Karim and Noy 2014).…”
Section: Introductionmentioning
confidence: 99%